PENGARUH METODE DRILL TERHADAP KETERAMPILAN MENULIS HURUF ARAB SISWA (PENELITIAN PADA SISWA KELAS IV DI SDI AL-ANHAR KARAWANG) - Rahmawati, Suci; Taufik Mustofa; M.Makbul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the drill method on the Arabic letter writing skills of fourth-grade students at SDI Al-Anhar Karawang. The research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest design. The population consisted of 35 students, all of whom were selected as the research sample through saturated sampling techniques. Data were collected through tests and documentation. The test instruments consisted of pretests and posttests used to measure students’ Arabic writing skills, including the accuracy of letter forms, the ability to connect letters, neatness of writing, and writing accuracy. The data were analyzed using descriptive and inferential statistics through normality tests and Paired Sample t-tests with the assistance of SPSS software. The results showed that the application of the drill method had an effect on improving students’ Arabic letter writing skills. This was indicated by the difference between pretest and posttest results after the implementation of the drill method. Therefore, the drill method can be used as an alternative teaching method to improve Arabic letter writing skills among Islamic elementary school students.